2019
DOI: 10.1182/blood-2019-131529
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Promyelocytic Leukemia in Brazil: Epidemiology, Molecular Features, and Importance of GST-Theta 1 in Chemotherapy Response and Outcome

Abstract: Background. Previous studies have suggested a variation in the incidence of acute promyelocytic leukemia (APL) among geographic regions with relatively higher percentages within the Latin American population. We aimed to describe the population burden of pediatric APL (p-APL) in Brazil assessing the incidence rates according to a hospital-based and population-based cancer (PBCR) registries. We also explored mutations in genes of the RAS pathway and the association of polymorphisms in genes of glutathione S-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…A total of 62 pediatric patients with ages less than 18, had APL out of 823 patients of AML (7.5%) were evaluable for our study and treated at Children Cancer Hospital Egypt, from July 2012 till the end of December 2019. In FG Andrade • 2021, 163 (17.5%) patients who had APL were evaluated out of 931 AML cases [11]. The median age of pediatric APL cases is from 9 to 12 years [12,13] agreed with our result as the median age was 9.9 years old, Thirty-one (50%) patients were more than 10 years old.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 62 pediatric patients with ages less than 18, had APL out of 823 patients of AML (7.5%) were evaluable for our study and treated at Children Cancer Hospital Egypt, from July 2012 till the end of December 2019. In FG Andrade • 2021, 163 (17.5%) patients who had APL were evaluated out of 931 AML cases [11]. The median age of pediatric APL cases is from 9 to 12 years [12,13] agreed with our result as the median age was 9.9 years old, Thirty-one (50%) patients were more than 10 years old.…”
Section: Discussionsupporting
confidence: 76%
“…Further family history and exposure to various agents via occupation or other risk factors should be studied to explain the epidemiological variation. [5] Verma et al…”
Section: Discussionmentioning
confidence: 99%
“…163 cases of APL were characterized (17.5 %) of a total of 931 cases of AML that presented a median age at diagnosis of 10.1 years. 25 In both cases, they found a higher incidence in southern Brazil, compared to the other geographic regions of the country; which could be associated with exposure to environmental factors, since the main economic activities in that area are agriculture and the oil and gas industry. 25 Aksu et al 8 reported an incidence of 20.5% among a total of 83 patients under 18 years of age who were diagnosed with AML in a hospital in Turkey, between January 2006 and December 2016, with a median of age at diagnosis of 13.5 years.…”
Section: Incidence Worldwidementioning
confidence: 93%
“…25 In both cases, they found a higher incidence in southern Brazil, compared to the other geographic regions of the country; which could be associated with exposure to environmental factors, since the main economic activities in that area are agriculture and the oil and gas industry. 25 Aksu et al 8 reported an incidence of 20.5% among a total of 83 patients under 18 years of age who were diagnosed with AML in a hospital in Turkey, between January 2006 and December 2016, with a median of age at diagnosis of 13.5 years. Czogala et al 9 observed that in Poland 41 children under 18 years of age were diagnosed with APL out of a total of 627 patients in that age range who were diagnosed with AML in the period between January 2005 and December 2018, for an incidence of 6.5%.…”
Section: Incidence Worldwidementioning
confidence: 93%
See 1 more Smart Citation